Improving school attendance - Hallam, Susan (India : Heinemann publishers, 1996)
This book will be the first in several years concerned with non-attendance. Previously unpublished material in the book will provide a multi-disciplinary evaluation of practice at LEA, whole school and individual levels
Includes index.
Keywords: School attendance -- Great Britain